Local flap for reconstruction of nasal defect following excision of basal cell carcinoma of nose (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Reconstruction of soft tissue at the nose following excision of basal cell carcinoma is always challenging, because of both functional and aesthetic importance of nose. The local flap is always preferable to skin graft as this produces like with like replacement, pliable cover and vascularized tissue over the skeletal framework. In this paper, we discussed six cases of nasal reconstruction with bilobed flap, forehead flap, and nasolabial flap. All flaps survived and the patients had satisfactory outcome.